Report of a Working Group on Barley: Sixth meeting, 3 December 2000, Salsomaggiore, Italy - Knüpffer, H.; Bothmer, R. von; Ambrose, M.; Ellis, R.; Stanca, A.M.; Enneking, D.; Maggioni, L.; Lipman, E.; European Cooperative Programme for Plant Genetic Resources; International Plant Genetic Resources Institute (2001)
These proceedings outline the discussions and recommendations made at the working group and contains the collection of presented papers from the meeting. Main topics of discussion include the European Barley Database (EBDB), the status of national collections, sharing responsibilities for conservation and promoting the use of barley genetic resources.